Direct RNA-based detection and differentiation of CTX-M-type extended-spectrum β-lactamases (ESBL). - Claudia Stein (Public Library of Science (PLoS), 2013)
The current global spread of multi-resistant Gram-negatives, particularly extended spectrum β-lactamases expressing bacteria, increases the likelihood of inappropriate empiric treatment of critically ill patients with subsequently increased mortality. From a clinical perspective, fast detection of resistant pathogens would allow a pre-emptive correction of an initially inappropriate treatment. Here we present diagnostic amplification-sequencing approach as proof of principal based on the fast molecular detection and correct discrimination of CTX-M-β-lactamases, the most frequent ESBL family. The workflow consists of the isolation of total mRNA and CTX-M-specific reverse transcription (RT), amplification and pyrosequencing. Due to the high variability of the CTX-M-β-lactamase-genes, degenerated primers for RT, qRT as well as for pyrosequencing, were used and the suitability and discriminatory performance of two conserved positions within the CTX-M genes were analyzed, using one protocol for all isolates and positions, respectively. Using this approach, no information regarding the expected CTX-M variant is needed since all sequences are covered by these degenerated primers. The presented workflow can be conducted within eight hours and has the potential to be expanded to other β-lactamase families.